Building Brand Loyalty: The Role of Brand Communication, Brand Identity, and Brand Experience Mediated by Brand Trust - Bawazir, Fatmah Cholid; Harianto, Eric; Azizurrohman, Muhammad (Universitas Brawijaya, Indonesia, 2024)
Sarung Mangga is a sarung brand produced by PT Panggung Jaya Indah Textile (PAJITEX), located in Pekalongan City, Central Java, Indonesia. Sarung Mangga has the problem of inefficient and effective branding budgeting, so branding objectives have not been achieved optimally. This study aims to determine the effect of brand communication, brand identity, and brand experience on brand loyalty mediated by brand trust in Sarong Mangga. This study uses quantitative methods, such as the purposive sampling technique. The sample in this study consisted of 497 respondents, namely, Sarong Mangga buyers. The data collection technique used a questionnaire and was analyzed using Smart PLS. The results of this study indicate that brand communication has no positive effect on brand trust, brand identity has a positive effect on brand trust, brand experience has a positive effect on brand trust, brand communication has no positive effect on brand loyalty, brand identity has a positive effect on brand loyalty, brand experience has a positive effect on brand loyalty, there is no significant influence between brand communication and brand loyalty through brand trust, there is a significant influence between brand identity and brand loyalty through brand trust, and there is a significant influence between brand experience and brand loyalty through brand trust. The implication of the research can contribute to enhancing brand loyalty in the textile industry. This can be achieved by developing strategies to create a positive consumer experience, build consumer trust, and foster strong consumer loyalty to the textile product brand.